STRATEGI PROGRAM SIARAN JEJAK ISLAM TVRI SULAWESI SELATAN - MUKRIMAH; ANDI MUH. FADLI; SURYANI MUSI (Jurnal Washiyah, 2026)
This study examines the broadcasting strategy of the Jejak Islam (Traces of Islam) program at TVRI South Sulawesi, focusing on two issues: (1) the forms of programming strategies applied, and (2) the supporting and inhibiting factors in their implementation. A descriptive qualitative method was employed with a mass communication approach. Data were collected through observation, in-depth interviews, and documentation involving six key informants at TVRI South Sulawesi, and analyzed using Miles and Huberman's interactive model. The findings reveal that the Jejak Islam program's strategy operates through seven aspects: a travel-documentary format combining storytelling with expert talkshow segments; a cross-generational audience target approach featuring modern cinematography; strategic broadcast scheduling on Tuesdays, Thursdays, and Saturdays at 18:29 WITA during the pre-iftar period; Islamic historical content thematic selection based on South Sulawesi's rich local heritage; a three-phase production process under budget constraints; multiplatform distribution via conventional television, YouTube, Instagram, and Facebook; and a rerun mechanism mandated by the national TVRI headquarters every Ramadan. Supporting factors include the Ramadan momentum, rich Islamic heritage of South Sulawesi, experienced human resources, adequate infrastructure, and regulatory support. Inhibiting factors encompass intense competition from commercial TV and digital platforms, limited budget and human resources, and the perception among younger audiences that TVRI is outdated. Keywords: Broadcasting Strategy, Jejak Islam, TVRI South Sulawesi, Mass Communication, Media Da'wah